Persepsi Minat Pembelian Mahasiswa Muslim Generasi Z ditinjau dari promosi dengan adanya BTS attractiveness dan kualitas web - Abdul Gofur; Hanuna Shafariah (LPMP Imperium, 2023)
The boyband group, which once shook the world of Bangtan Sonyeondan (BTS) music, has become the interest of entrepreneurs to carry out promotions by attracting them to become representatives of their products or shops. So this study aims to determine the attractiveness of BTS with promotions and combined with web quality interactions in influencing Generation Z's purchase intention on Tokopedia. The target population is Tokopedia consumers who are included in the Z generation who are members of students at three campuses in Jakarta. Samples were obtained by 104 respondents with snowball sampling, rolling from three campus representatives. The results obtained are that both the promotion and the attractiveness of BTS directly influence purchase intention. While web quality does not have a significant direct effect on purchase intention. The moderation of the attractiveness of BTS strengthens while the quality of the web weakens the promotion's influence on purchase intention. Future research needs to examine more deeply the relationship between web quality and generation Z and also interactions with promotions on purchase intention.Public interest statementIn this research, we try to put forward a model regarding the interaction of attractiveness of brand ambassadors and promotions as well as we b quality on purchase intention.Article HistoryReceived: 11 Apr 2023 | Revised: 25 Apr 2023 | Accepted: 03 May 2023 | Online First: 05 May 2023 .